PEMBELAJARAN BAHASA ARAB BERBASIS KITAB KUNING DI KELAS TIMUR TENGAH MADRASAH ALIYAH NEGERI 1 PEKANBARU - Reni Dwita Putri; Riko Andrian (Universitas Muhammadiyah Makassar, 2026)
Arabic language learning based on kitab kuning in formal educational institutions faces unique challenges, ranging from differences in students' foundational abilities to the limited availability of competent teaching staff. This study aims to examine the implementation of kitab kuning-based Arabic language learning in the Middle East Class at MAN 1 Pekanbaru, encompassing planning, organizing, implementation, evaluation, as well as its supporting and inhibiting factors. The study employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation, subsequently analyzed through data reduction, data presentation, and conclusion drawing. The findings indicate that the learning process takes place systematically through four stages: planning in the form of lesson plan (RPP) development oriented toward kitab kuning reading proficiency; organizing through role distribution, scheduling, and adequate facilities; implementation that integrates the bandongan and sorogan methods with modern approaches in an interactive manner; and evaluation emphasizing practical competencies in reading and translating classical Arabic texts. Supporting factors include a structured class program, institutional support, and the pesantren background of a portion of the students, while inhibiting factors encompass student ability heterogeneity, heavy academic workload, and the limited availability of substitute teachers. This study concludes that the integration of kitab kuning into the formal Arabic language curriculum at MAN 1 Pekanbaru is effective in enhancing students' classical Arabic literacy and opening pathways for further study at higher education institutions in the Middle East.